Teacher Support and Mental Well-Being in Chinese Adolescents: The Mediating Role of Negative Emotions and Resilience - Guo, Junqiao (Front Psychol, 2020)
Teacher support has been shown to enhance adolescent mental health. However, the effects of negative emotions and resilience in the relationship between teacher support and mental well-being in adolescents are still unknown. This study investigated (a) the mediating role of negative emotions in the relationship between teacher support and mental well-being, (b) the mediating role of resilience in the association between teacher support and mental well-being, (c) the serial mediating role of negative emotions and then resilience in the relationship between teacher support and mental well-being, and (d) the parallel mediating role of the five dimensions of resilience and the three factors of negative emotions in the relationship between teacher support and mental well-being. Participants were 1228 Chinese adolescents (age, M = 15.43 years; 53.09% male). Participants filled out questionnaires regarding teacher support, negative emotions, resilience, and mental well-being. After controlling for age and gender, we found that teacher support, negative emotions, and resilience were significantly linked with mental well-being. Moreover, negative emotions and resilience were found to mediate the relationship between teacher support and adolescent mental well-being, accounting for 5.45 and 30.00% of the total effect, respectively. We also found that teacher support enhances mental well-being by decreasing negative emotions and then increasing resilience. This serial mediating effect accounted for 8.48% of the total effect. Finally, the mediating effect of resilience between teacher support and mental well-being was significantly greater than the mediating effects of the other two indirect effects (negative emotions in the relationship between teacher support and mental well-being, negative emotions and then resilience in the relationship between teacher support and mental well-being). And the parallel mediation model showed that teacher support can promote adolescent mental well-being by increasing goal planning, affect control, and help-seeking behavior, and decreasing depression. These findings suggest a process through which negative emotions can decrease resilience and identify the mediating effects of negative emotions (including the three dimensions of negative emotions) and resilience (including the five factors of resilience) in the relationship between teacher support and adolescent mental well-being.